PENGEMBANGAN MEDIA PEMBELAJARAN KAKLI (KARTU KWARTET LITERASI) PADA MATERI SUMBER DAYA ALAM - Safitri, Shella; Putra, M. Jaya Adi; Hermita, Neni (STKIP Pesisir Selatan, 2022)
The product produced by this development research is a learning media in the form of a quartet card on Natural Resources material. This learning media product was created and designed with the aim that it can be applied as a teacher's tool in delivering material, literacy activities and as a source of independent learning by students. The purpose of this research is to produce a product for developing Kakli learning media (Quartet Literacy Cards) on Natural Resources material. This research is included in research and development (R&D) using the ADDIE model (Analyze, Design, Development, Implementation, Evaluation) because it is seen as a suitable design model for the development of learning media in the form of this Literacy Quartet Card. The data collection instrument used in the study was a questionnaire (questionnaire). In this research and development, researchers conducted quantitative and qualitative data analysis. The results of the research conducted, it can be concluded as follows: The media of the natural resource material literacy quartet card is classified as very valid with a score of 83% for material validation, and for the validation of the natural resource material literacy quartet card media it is declared a valid category so that it has met validity criteria and can be used in schools, then categorized in the game media which is very feasible in the teacher response test and student response test with a score of 92% and 86.33%, which is above 81.25%